Can Bigger Be Safer? Firm Size and Financial Ratios in Distress Prediction - Rahmah, Tarissa Aqilla; Akbar, Fajar Syaiful (Economics, Business, Accounting & Society Review, 2025)
The declining performance of Indonesia’s consumer cyclicals sector, highlights the sector’s increasing exposure to financial distress amid global economic slowdown and inflationary pressures. Previous studies have largely focused on manufacturing firms and leverage variables, leaving a research gap concerning liquidity, profitability, and firm size as predictors of financial distress in post-pandemic market conditions. This study aims to examine the effect of liquidity, profitability, and firm size on financial distress among consumer cyclicals companies listed on the Indonesia Stock Exchange between 2021 and 2023. A quantitative approach was employed using purposive sampling, resulting in 117 firm-year observations. Financial distress was measured by the modified Altman Z″-Score, while multiple linear regression was used to test the hypotheses after confirming classical assumptions. The results reveal that liquidity and firm size have a significant negative effect on financial distress, whereas profitability exerts a positive influence, suggesting that higher profits may not always translate into financial stability if accompanied by inefficient capital or debt management. Collectively, these variables explain 64.5% of the variation in financial distress, confirming their combined predictive relevance. The study contributes to the refinement of signaling and agency theory by demonstrating that liquidity and firm size act as stabilizing signals of financial health, whereas profitability may misrepresent true resilience. Practically, the findings guide investors, managers, and regulators in developing risk-mitigation and monitoring strategies to strengthen financial sustainability in volatile sectors.